2022
DOI: 10.1002/er.7890
|View full text |Cite
|
Sign up to set email alerts
|

Design optimization of a heat‐to‐cool Stirling cycle using artificial neural network

Abstract: This study focuses on applying artificial neural network (ANN) to investigate different parameters and operating conditions that affect the cooling flux and efficiency of a heat-to-cool gamma-type Stirling machine. ANN model is developed to predict output parameters of the Stirling machine based on sample data generated by a MATLAB code-named Nlog code. The code was previously developed and validated by the authors. To reach the addressed goal, three input parameters, including Stirling refrigerator frequency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Artificial neural network (ANN) has been applied to study the effect of different parameters and operating conditions for the heat-to-cool gamma-type Stirling machine [28]. It has been reported that ANN model could predict the performance of a Stirling machine accurately and within a reasonable time.…”
Section: Introductionmentioning
confidence: 99%
“…Artificial neural network (ANN) has been applied to study the effect of different parameters and operating conditions for the heat-to-cool gamma-type Stirling machine [28]. It has been reported that ANN model could predict the performance of a Stirling machine accurately and within a reasonable time.…”
Section: Introductionmentioning
confidence: 99%
“…AI algorithms can automate the analysis and optimization of complex structures, enabling engineers to quickly evaluate different design options and identify optimal solutions. Additionally, AIbased predictive modeling techniques allow engineers to assess the performance of structures under different loads and environmental conditions [3].…”
Section: -Introductionmentioning
confidence: 99%
“…Integration Complexity: Integrating AI techniques into existing civil engineering programs and drawing techniques may pose technical challenges. Compatibility issues, software integration, and interoperability need to be addressed to ensure smooth integration and seamless workflow[3]. 7.…”
mentioning
confidence: 99%